Timing matters: Distinct effects of nitrogen and phosphorus fertilizer application timing on root system architecture responses. Issue 4 (22nd July 2021) - van Duijnen, Richard; Uther, Hannah; Härdtle, Werner; Temperton, Vicky M.; Kumar, Amit
Abstract: Aims: Although different plant foraging responses to the two macronutrients nitrogen (N) and phosphorus (P) are well researched, the effect of timing of fertilizer application on root system architecture (RSA) remains largely unknown. We, therefore, aimed to understand how RSA of Hordeum vulgare L. responds to timing of N and P application. Methods: Plants were grown in rhizoboxes for 38 days in nutrient‐poor soil and watered with nutrient solution, lacking either N or P, with the absent nutrient applied once either 2/3/4 weeks after sowing. Positive controls were continuously receiving N and P and a negative control receiving both N and P only after 3 weeks. We tracked root growth over time, measured plant biomass and nutrient uptake. Results: Late N application strongly reduced total root biomass and visible root length compared with continuous NP and late P application. Root mass fractions (total root biomass/total plant biomass) remained similar over all treatments, but relative allocation (% of total root biomass) was higher in lower depth with late N application. Shoot P concentrations remained relatively stable, but the plants receiving P later had higher N concentrations. Conclusions: Late N application had overall more negative effects on early plant growth compared with late P. We propose that future studies under field conditions should try to disentangle the effect of timing from the nutrient availability on RSA responses and hence ultimately plant performance.